MacGregor Grooms - Roberts, Nora (New York : Silhouette Books, 1998)
In this sequel to her "New York Times" bestseller "The MacGregor Brides", Nora Roberts one again brings readers back to the warmth and charm of her beloved MacGregor family. Daniel MacGregor continues his matchmaking shenanigans as he sets out to prove to his three grandsons that he has an unerring instinct for love.
"MacGregor family saga"--P. 4 of cover.
79292
Keywords: Contemporary Romance; MacGregor family; Love stories